(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In this article, the unevenness of moisture content in the storage of high-moisture cottons in cotton ginning enterprises is studied, and the effect of this unevenness on the production process is considered.